P-265 Palliative care clinical nurse specialist: a new addition to the hospice inpatient unit team. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Chan, Lily; Walker, Simon; Fletcher, Andrew
Abstract : Background: In December 2014 the hospice introduced the role of CNS on to the inpatient unit. The role involves working closely with the medical team in admission and management of patients whilst providing mentorship and education to nursing staff and junior doctors. Aim: To determine the effectiveness and impact of the CNS role on the hospice inpatient unit. Methods: An online anonymous survey of the multidisciplinary inpatient team. Results: 18 members of the multidisciplinary team responded. 28% of staff understood the CNS role very well with 72% moderately well. All staff found the addition of the CNS role to be useful with 78% feeling the role was very or extremely useful. 72% and 67% of staff found the role to be of great value to patients and their families respectively whilst 71% felt one of the most valuable aspects of the role was being a link between the medical and non-medical teams. Comments highlighted the nursing experience and clinical knowledge of the CNS to be of particular benefit. Having CNS input within the medical team offers a different perspective on case management. Discussion: The survey results and experience of the team support the conclusion that the introduction of the CNS role on the hospice inpatient unit has been highly effective for patients, their families and the multidisciplinary team. The CNS had completed a clinical assessment and diagnostics qualification prior to commencing the role which proved to be of great value and would be seen as a very desirable qualification in the future. Since commencing the role, the CNS is now a non-medical prescriber which is proving to be of significant benefit. Later in the year, training for the non-medical prescribing of blood components will be completed. A survey of patients and families views is also to be undertaken.